The Effect of Lean on Improving the Quality of Higher Education in Indonesia - Andri oktarian; Dadang Surjasa (Universitas Trisakti, 2021)
Higher education essentially needs to pay attention to the quality of its graduates, whether it is by the current market demand for the world of work. To provide a quality education service, it is not enough to make improvements within the tertiary institution. In general, Lean management in tertiary institutions has 3 fields, namely the field of education, the field of research, and the field of service. The principles and practices of Lean management applied in universities are the same as those applied to the service, manufacturing, or government sectors. To eliminate wasted time, it is necessary to eliminate complexity, cost, or activities that do not add value. Lean principles such as just-in-time can be applied to a better quality of learning and research. This paper examines how Lean principles can be applied to education and research in universities - Lean Higher Learning and Lean Research with a focus on value flow analysis for better quality improvement of learning and research.